2002
DOI: 10.1016/s0002-9440(10)61118-2
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood and Granuloma CD4+CD28− T Cells Are a Major Source of Interferon-γ and Tumor Necrosis Factor-α in Wegener’s Granulomatosis

Abstract: To elucidate whether the fraction of CD28(-) T cells within the CD4(+) T-cell population is a major source of Th1-like and proinflammatory cytokine production driving Wegener's granulomatosis (WG) granuloma formation, we analyzed the phenotype and functional characteristics of peripheral blood CD4(+)CD28(-) T cells and of T cells in granulomatous lesions of 12 patients with active WG. Surface markers and intracytoplasmic cytokine and perforin expression were assessed by flow cytometry. Cytokine secretion was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
159
1
11

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 194 publications
(184 citation statements)
references
References 38 publications
(39 reference statements)
12
159
1
11
Order By: Relevance
“…Other investigators have observed differences in the expression of chemokines and chemokine receptors across disease subsets (42,43). In addition, some studies are consistent with confinement of critical cytokine production to certain T cell subsets, and recruitment of such cells (particularly CD28-negative T cells) into granulomatous lesions of patients with WG (44,45).…”
Section: Discussionmentioning
confidence: 60%
“…Other investigators have observed differences in the expression of chemokines and chemokine receptors across disease subsets (42,43). In addition, some studies are consistent with confinement of critical cytokine production to certain T cell subsets, and recruitment of such cells (particularly CD28-negative T cells) into granulomatous lesions of patients with WG (44,45).…”
Section: Discussionmentioning
confidence: 60%
“…These T cells have undergone clonal expansion in vivo, have lost the expression of CD40L, are highly proinflammatory, and express a variety of killer Ig-like receptors (10 -14). An expansion of CD4 ϩ CD28 null T cells was also reported for patients with other autoimmune diseases (13,15), HIV-and CMV-infected individuals (16), and people suffering from coronary disease (17). Although the role of these cells in disease pathology is not clear, CD4…”
Section: T He Cd4mentioning
confidence: 55%
“…ϩ CD28 Ϫ cells, present in granulomas, seem to contribute to production of IFN-␥ and TNF-␣ (77,78). These cells show evidence of an effector-memory phenotype, oligoclonality, and replicative senescence, suggesting that they are the product of antigen exposure but not necessarily MPO or PR3 (78,79) (reviewed in [80]).…”
Section: Cd28mentioning
confidence: 99%